2023
DOI: 10.21203/rs.3.rs-3074292/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Prevalence of Anemia Post-COVID-19 Infection in Adult Members of a Southeastern U.S. Integrated Healthcare System

Alexander F. Hudgins,
Bennett McDonald,
Patricia A. Bush
et al.

Abstract: Background COVID-19 may cause or worsen anemia, leading to fatigue, lower quality of life, increased risk of comorbidities, and significantly associated with worse outcomes in patients hospitalized with COVID-19. Little is known among a community-based population. We aimed to investigate the incidence and risk factors of anemia post-COVID diagnosis in a community-based population. Methods We identified all adult members of KPGA with a confirmed diagnosis of COVID-19 between January 2020 and March 2022 and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…The present study agrees with the negative effects of severe COVID-19 on red cell parameters, as this has been described by earlier studies where RBC, HCT, and Hb were reduced in Ghana [40,41] and other parts of the world [4][5][6][7]. The 58.6% prevalence of anaemia among COVID-19 patients recorded in this study is higher than the 19.23% identified in Liaocheng, China [42], 35.6% [43], and 38.2% [44] of hospitalized COVID-19 patients in Wuhan, China, and 42.7% among COVID-19 survivors in a 30-day prospective cohort study during the initial wave of the outbreak in Italy [5].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study agrees with the negative effects of severe COVID-19 on red cell parameters, as this has been described by earlier studies where RBC, HCT, and Hb were reduced in Ghana [40,41] and other parts of the world [4][5][6][7]. The 58.6% prevalence of anaemia among COVID-19 patients recorded in this study is higher than the 19.23% identified in Liaocheng, China [42], 35.6% [43], and 38.2% [44] of hospitalized COVID-19 patients in Wuhan, China, and 42.7% among COVID-19 survivors in a 30-day prospective cohort study during the initial wave of the outbreak in Italy [5].…”
Section: Discussionsupporting
confidence: 93%
“…The 58.6% prevalence of anaemia among COVID-19 patients recorded in this study is higher than the 19.23% identified in Liaocheng, China [42], 35.6% [43], and 38.2% [44] of hospitalized COVID-19 patients in Wuhan, China, and 42.7% among COVID-19 survivors in a 30-day prospective cohort study during the initial wave of the outbreak in Italy [5]. The prevalence is, however, lower compared to the 62.8% found in a retrospective study in Riyadh, Kingdom of Saudi Arabia [6], 66.7% among COVID-19 non-survivors in Italy [5], and 74.3% from the CURE cohort (from Kaiser Permanente Georgia's (KPGA) electronic medical record (EMR), which used data generated from members of a southeastern integrated healthcare system testing positive for COVID-19 [7]. The anaemia may be due to the COVID-19-associated cytokine storm that influences iron absorption and re-uptake, and inhibits erythropoietin.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our binary logistic regression analysis underscores that on-admission anemia, lower Hb levels, and reduced MCH levels are significant predictors of post-COVID anemia. This agrees with the study of Hudgins et al (2023) (34) who demonstrated that anemia on admission was a significant risk factor for the prolonged presence of anemia in post-COVID patients. Identifying individuals at higher risk and implementing appropriate interventions, such as iron supplementation or other treatments-is crucial in managing and reducing the incidence of anemia in individuals recovering from COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, of Hudgins et al (2023) (34) highlighted the prolonged presence of anemia in post-COVID patients, drawing attention to the large proportion (about one in three) of individuals diagnosed with COVID-19-displaying signs of anemia at both the 180-day and 365-day marks postinfection.…”
Section: Discussionmentioning
confidence: 92%